2020
DOI: 10.3389/fimmu.2020.01259
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles for Chemokines in Neutrophil Biology

Abstract: Chemokines are recognized as the most critical mediators for selective neutrophil recruitment during inflammatory conditions. Furthermore, they are considered fundamental regulators of neutrophil mobilization from the bone marrow (BM) to the bloodstream and for their homing back at the end of their life for apoptosis and clearance. However, chemokines are also important mediators of neutrophil effector functions including oxidative burst, degranulation, neutrophil extracellular trap (NET)osis, and production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 98 publications
4
125
0
Order By: Relevance
“…In line with results from previous literature, expression levels of certain chemokines were increased after LPS injection in this study; in specific, among the aforementioned chemokines, CXCL1 and CCL2 demonstrated a surge in expression, along with CXCL13, CXCL10, and CCL5. CXCL1 and CCL2 are well-known for their roles in stimulating neutrophil migration, while CXCL10, CCL2, and CCL5 have been reported to be released by neutrophils in inflammatory situations, mostly in order to recruit other innate or adaptive immune cells ( Kobayashi, 2008 ; Sawant et al, 2016 ; Capucetti et al, 2020 ). Therefore, chemokines that are chemotactic for neutrophils, such as CXCL1 or CCL2 may be the principal factor driving the various migratory phenomena observed in this paper: neutrophil extravasation and rTEM.…”
Section: Discussionmentioning
confidence: 99%
“…In line with results from previous literature, expression levels of certain chemokines were increased after LPS injection in this study; in specific, among the aforementioned chemokines, CXCL1 and CCL2 demonstrated a surge in expression, along with CXCL13, CXCL10, and CCL5. CXCL1 and CCL2 are well-known for their roles in stimulating neutrophil migration, while CXCL10, CCL2, and CCL5 have been reported to be released by neutrophils in inflammatory situations, mostly in order to recruit other innate or adaptive immune cells ( Kobayashi, 2008 ; Sawant et al, 2016 ; Capucetti et al, 2020 ). Therefore, chemokines that are chemotactic for neutrophils, such as CXCL1 or CCL2 may be the principal factor driving the various migratory phenomena observed in this paper: neutrophil extravasation and rTEM.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings on CXCR2 surface level, our study fails to demonstrate the changes of CD64 and CCR2 surface levels as sepsis-related. CD64 and CCR2 receptors are not constitutively expressed on neutrophils at resting state (15,25); however, earlier studies showed that CD64 and CCR2 surface levels were increased during sepsis (3). The amount of CD64 mRNA elevates to a measurable level within 1-3 h of the inciting events leading to a significant increment of CD64 surface level within 4-6 h (13).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils perform their effector activities after migration into peripheral tissues. Circulating CXCR1 + CXCR2 + mature neutrophils are orchestrated to tissues by gradients of CXCL1, CXCL2, CXCL8, CCL3, and CCL2 ( 26 ). Binding of these chemokines does not only guide the localization, but also activates them as demonstrated by CXCL8 that can elicit ROS production and induce L-Selectin shedding ( 27 ).…”
Section: Neutrophil Function In Health and Diseasementioning
confidence: 99%